Asperfurandiones A and B, two antifungal furandione analogs from a marine-derived fungus Aspergillus versicolor. Issue 23 (2nd December 2019) - Ding, Lijian; Xu, Peng; Li, Te; Liao, Xiaojian; He, Shan; Xu, Shihai
Abstract: Two new furandione derivatives, designated as asperfurandiones A (1 ) and B (2 ), were isolated from the solid culture of the marine-derived fungus Aspergillus versicolor . Their structures were elucidated using a combination of mass spectrometry and NMR spectroscopy. Additionally, asperfurandiones A and B both showed moderate antifungal activity against Gaeumannomyces graminis, Cryptococcus neoformans, and Candida albicans with MIC values of 64 μg/mL. Abstract :